Identification of Risk Factors for Testing of Hepatitis C in Non-Birth Cohort Patients: Is Universal Screening Necessary?. Issue 2 (March 2021) - Smart, Amanda; Geboy, Alexander; Basch, Peter; Nichols, Whitney; Zeymo, Alexander; Perez, Idene; Hafeez, Maria; Fleisher, Ilan; Fernandez, Stephen; Fishbein, Dawn
Abstract : Objectives: CDC reported that 45% of Hepatitis C (HCV) infected people denied known risk factors. Electronic health record RF-based, non-Birth Cohort (born outside of years 1945–1965) screening is challenging as risk factors are often input as nonsearchable data. Testing non-Birth Cohort patients solely based on risk factors has the potential to miss a substantial number of HCV infected patients. The aim was to determine the HCV antibody positive prevalence who would have been missed had providers only followed risk factor based screening recommendations. Methods: A 1:3 case-control retrospective nested chart review was conducted. HCV risk factors and opioid prescriptions were manually abstracted from the Electronic Health Record; other variables were collected using Explorys. In July 2015 HCV screening data was collected on non-Birth Cohort patients who were HCV tested across MedStar Health, as a presumptive marker for high risk. Univariate and multivariate logistic regression models were utilized to determine HCV antibody positive predictors. Results: Eighteen (23%) HCV antibody positive and 123 (49%) HCV antibody negative had no identified risk factors; 6 (33%) HCV antibody positive reported risk factors only after a positive test result. There was a significant interaction between age over 40 and opioid prescription use; these groups were 11× more likely to be HCV antibody positive (CI95 1.6–74.8). Conclusions: HCV testing solely based on presence of risk factors in non-Birth Cohort patients has the potential to miss a significant number of HCV antibody positive patients. Given patient- and provider-level barriers in elucidating risk factors, universal HCV antibody screening may be warranted.